Unifocal tubercular osteomyelitis of distal ulna: a rare presentation. (11th January 2012) - Shantanu, Kumar; Sharma, Vineet; Kumar, Santosh; Jain, Sonal
Abstract : Tuberculosis is a major health issue in developing countries. The authors present a case of a 28-year-old male doctor, working as resident in the department of radiodiagnosis who attended orthopaedics outdoor with complaint of wrist pain over ulnar aspect. Radiograph of left wrist showed an oval shaped osteolytic lesion. Fine needle aspiration cytology was performed which produced only haemorrhage. Therefore, open biopsy was planned; yellowish coloured material was obtained which was sent for histopathological examination. Finally, Mycobacterium tuberculosis was isolated and thus the patient was immediately started with antitubercular therapy. This brief report emphasises upon the rare sites of skeletal tuberculosis which should always be kept in mind while diagnosing such lesions.